Comparative Analysis of Service Quality and Customers’ Satisfaction of Interest - and Non-Interest - Based Cooperative Societies in Ilorin Emirate - Mustapha, Ismaila; Aremu, Mukaila; Brimah, Aminu (Jordan Journal of Business Administration, 2017)
Dissatisfaction of customers (members) with the quality of service of cooperative societies in the recent past has put their growth and survival in question. The need for qualitative service has caused customers to join different types of cooperative societies with different modes of operations, especially interest - and non-interest- based cooperative societies. This study specifically examines the difference between service quality and level of satisfaction derived by members of interest - and non-interest- based cooperative societies, as well as the relationship between service quality and members’ level of satisfaction. It employed a combination of stratified and convenience sampling techniques to select 180 target respondents from the study area. Independent t-test and regression analysis were employed as analytical techniques. The study found that there is a difference between service quality and satisfaction level of members of interest - and non-interest- based cooperative societies and that there is a significant relationship between service quality and satisfaction level of members of cooperative societies. It was recommended that managers of the two categories of cooperative societies should explore the service quality dimensions as means of competitive advantage in their respective areas of operations.